Effect of water quality on ice hardness and skate-to-ice friction in ice rinks - Hutchins, R. H. S.; Wang, J.; Impellizzeri, S. (Sports Engineering, 2026)
Ice hardness and friction influence performance and safety in ice sports, yet the role of water quality remains poorly understood. This study examines how total dissolved solids in rink water affect ice characteristics using nondestructive hardness testing and a skate-to-ice static friction index measured under controlled rink conditions. Results show that temperature influences ice hardness and static friction, with colder ice being harder and exhibiting higher static friction. Water quality also plays a role, as lower total dissolved solid levels reduce static friction, with effects comparable to a 1C increase in ice temperature. However, ultra-pure water produced softer ice, while moderate total dissolved solid levels maintained ice hardness with minor static friction increases. These findings support hockey rink recommendations to maintain total dissolved solids near 80 to 100 ppm to balance ice hardness with friction performance. However, other sports, such as curling, may benefit from lower total dissolved solids for reduced static friction. Understanding these relationships informs best practices in rink maintenance and water treatment.